Analysis Of The Success Of The MSMEs Jenang Karomah Industry In Kaliputu Village, Kudus Regency - Afrizal Yonanta Chavis Abel; Muhammad Feriady (LPPM STMIK Mardira Indonesia, 2026)
This study aims to identify the determining factors for the success of Jenang Karomah MSMEs in Kudus Regency. This study uses a descriptive method with a qualitative approach. Data collection was carried out through observation, interviews, and documentation. Data analysis was carried out using the Spradley model through domain analysis, taxonomy, componential analysis, and cultural theme stages. The results of the study indicate that the success of Jenang Karomah MSMEs is influenced by the implementation of the 4P marketing mix strategy which includes product quality, appropriate pricing, easily accessible locations, and promotions carried out directly and through digital media. In addition, a production strategy that maintains consistent taste and product quality, managerial skills in managing the business, and government support also contribute to improving business sustainability. Customer orientation is also an important factor, because good service and meeting consumer needs can create customer loyalty. It is recommended that Jenang Karomah MSMEs increase the use of digital marketing and expand cooperation with online sales platforms to expand market reach and improve business competitiveness.